Empirical studies for validating class diagram metrics - Genero, Marcela (2002)
The quality of class diagrams is crucial for all later design work and could be a major determinant for the quality of the software product that is finally delivered. In order to assess class diagram quality in an objective way it is necessary to have quantitative measurement instruments. This paper presents a set of metrics which measure UML class diagram structural complexity based on the use of UML relationships. Also it summarizes two controlled experiments carried out in order to corroborate if those metrics are related with UML class diagram maintainability. The findings obtained trough the experimentation reveal that most of the metrics we proposed (NAssoc, NAgg, NaggH, MaxHAgg, NGen, NgenH and MaxDIT) might be good indicators of class diagram maintainability. We cannot, however, draw such firm conclusions regarding the NDep metric.